Planting - Allpanchis, Revista (1971)
From very early, the workers congregate in the house of the owner of the farm, whom they call chajrachikoq, he who makes the farm work. There, they have lunch at 6 a.m. and they go out to sow, carrying their work tools: Inca plow or chaki tajlla, pickaxe, qorana, yoke with their respective straps, bars and their watos (leather strips to tie the barred); others herd the oxen, or wakamasas, while the women carry chombas de chicha, bottles of alcohol, on typical carts of the region. Arrived at the paddock, they tie up the teams and get the tools ready.